Hubungan Mutu Pelayanan dengan Kepuasan Pasien Poli Gigi Puskesmas di Kecamatan Guguk Panjang, Kota Bukittinggi - Rezza Marietha Zulmi; Denas Symond; Susi Susi (Andalas Dental Journal, 2022)
Background: Patient's perspective is one of the indicator that affect the health care quality. Best service of health provider is also important parameter to achieving the patient's satisfaction. Purpose: to determine the relationship of the dimensional service quality to dental patient satisfaction in Puskesmas Guguk Panjang, Bukittinggi. Method: This was a cross sectional study, participating of 106 respondents arround 25-65 years old. The patient who ever comes to the puskesmas Guguk Panjang were included to this study. The data were analyzed by Chi-Square test on a p-value of 0.05. Results: The most of respondents state the quality service of oral health care in Puskesmas Guguk Panjang Bukittinggi are good (80,2%). Statistically, there is significant relationship between quality service (tangibles, reliability, responsiveness, assurance, and empathy) to patient satisfaction. Thec cartesian diagram showed that there’s still some dimension haven’t meet the patients satisfaction and need to be fixed which consists of building and dental section’s appearance and sanitation, also lack of dental equipments. This research concluded that there is significant relationship between quality service to the dental patient satisfaction. Atributes in Quadrant I need to be evaluated and repaired.